Epigenetic silencing of LPP/miR-28 in multiple myeloma. Issue 3 (3rd August 2017) - Li, Zhenhai; Wong, Kwan Yeung; Chan, Godfrey Chi-fung; Chim, Chor Sang
Abstract : Aims: miR-28-5- is a tumour suppressor microRNA implicated in cancers. As a CpG island is absent in miR-28-5- but present in its host gene, LPP (LIM domain containing preferred translocation partner in lipoma), we hypothesized that miR-28-5p is epigenetically silenced by promoter DNA methylation of its host gene in multiple myeloma. Methods: Methylation-specific PCR, verified by quantitative bisulfite pyrosequencing, was employed to study methylation of LPP/miR-28 in healthy controls (n=10), human myeloma cell lines (HMCLs) (n=15), and primary myeloma marrow samples at diagnosis (n=49) and at relapse (n=18). Quantitative reverse transcription PCR was used to investigate expression of miR-28-5p, LPP and CCND1. Results: LPP/miR-28 was completely unmethylated in all healthy controls and 12 (80%) HMCLs, but partially methylated in three (20%) HMCLs. Methylation of LPP/miR-28 correlated with low expression of miR-285p (p=0.012) and LPP (p=0.037) in HMCLs. In RPMI-8226R cells, in which LPP/miR-28 was partially methylated, 5-AzadC treatment led to demethylation of LPP/miR-28 and re-expression of both miR-28-5p (p=0.0007) and LPP (p=0.0007), whereas continuous culture without 5-AzadC restored LPP/miR-28 methylation and reduced expression of both miR-28-5p (p=0.0013) and LPP (p=0.0025). Moreover, a known miR-28-5p target, CCND1, was expressed at higher levels in HMCLs with LPP/miR-28 methylation than those without, consistent with a tumour suppressor role of miR-28-5p in myeloma. However, in primary samples, LPP/miR-28 was methylated in two (4.1%) at diagnosis, whereas none at relapse. Conclusions: This is the first report of epigenetic regulation of the intronic miR-28-5p expression by promoter DNA methylation of its host gene, hence warrants further study in different cancers.